(untitled) (Studia Prawnicze / The Legal Studies, 2016)
Trybunały administracyjne powoływane przez organizacje międzynarodowe rozstrzygają spory pomiędzy organizacją a jej pracownikami. Zgodnie z art. 11 Statutu Trybunału Administracyjnego Organizacji Narodów Zjednoczonych (TAONZ) Komitet ds. Wniosków o Rewizję Orzeczeń TAONZ oraz zgodnie z art. XII Statutu i art. XII Aneksu do Statutu Trybunału Administracyjnego Międzynarodowej Organizacji Pracy (TAMOP) Rada Zarządzająca lub Rada Administracyjna Funduszu Emerytalnego mogły, w określonych w ich statutach przypadkach, zwrócić się do MTS o wydanie opinii doradczych. Opinie te miały wiążący charakter dla organizacji, które o nie wystąpiły. Od momentu utworzenia w 1927 r. pierwszego trybunału administracyjnego w ramach Ligi Narodów aż do 1 lipca 2009 r. rozwój trybunałów administracyjnych był determinowany zmianami w dziedzinie międzynarodowego systemu ochrony praw człowieka. Zmierzał w kierunku wyposażania tych trybunałów w środki gwarantujące, na równych zasadach dla wszystkich, prawo do sądu oraz sprawiedliwego procesu. Tylko bowiem w ten sposób można skutecz-nie zagwarantować ochronę praw jednostki także w sprawach pracowniczych. The International Court of Justice (ICJ) is a principal judicial organ of the United Nations. The main task of ICJ is to settle disputes submitted to it by the states and is also entitled to give advisory opinions which are given on the motion of some United Nations organs and specialized agencies. The expression that ICJ is a “principal judicial organ of the United Nations” doesn’t mean that it is the only one judicial organ within the framework of the United Nations. The United Nations Administrative Tribunal (UNAT) was established by the legal force of the General Assembly resolution 351 A(IV) of 9 December 1949 r. The main purpose of the UNAT was to decide legal employment disputes between United Nations staff and the Organization. In 1955 the Statute of UNAT was amended and the Committee on Application for Review of Administrative Tribunal Judgement was competent to seek advisory opinion form ICJ and this opinion was binding. However Committee only in three cases requested the ICJ to give advisory opinion. Those opinions concerned inter alia the competence of ICJ to respond to the question, the right of Committee to submit such motion, the principle of equality of arms. In spite of that since of the 1st of July 2009 the new system of administration of internal justice was established – the United Nations Dispute Tribunal and the United Nations Appeal Tribunal, which consider the appeals against judgments rendered by the United Nations Dispute Tribunal, the issues discussed in advisory opinions of ICJ on the matters of appealing against a judicial decision of UNAT are still highly topical, especially in the context of the maintained in force competence of ICJ to review judgement of The Administrative Tribunal of the International Labour Organisation.